2022
DOI: 10.3390/vaccines10091411
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis DNA Vaccines with Epitope Modification Reduce the Induction of Cross-Reactive Antibodies against Dengue Virus and Antibody-Dependent Enhancement of Dengue Virus Infection

Abstract: Infection with viruses belonging to the genus Flavivirus, such as Japanese encephalitis virus (JEV) and dengue virus (DENV), is a worldwide health problem. Vaccines against JEV and DENV are currently available. However, the dengue vaccine possibly increases the risk of severe dengue due to antibody-dependent enhancement (ADE). Moreover, the Japanese encephalitis (JE) vaccine reportedly induces cross-reactive ADE-prone antibodies against DENV, potentially leading to symptomatic dengue. Therefore, it is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Here, we demonstrated DII FL 106/107 residues were involved in inducing neutralizing antibodies against JEV and these two residues together with the 101 residue were involved in eliciting neutralizing antibodies against JEV and WNV. However, a recent study showed that JEV GIII VLP-expressing plasmids encoding single or double DII FL G106V and L107F mutations performed comparably to the wild-type plasmid in eliciting neutralizing antibodies against JEV ( 39 ). This discrepancy could be due to the use of different amino acids at the DII FL 106 and 107 residues, the method to measure neutralizing antibody titers, or the type of immunogens (VLP vs DNA) used in the study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we demonstrated DII FL 106/107 residues were involved in inducing neutralizing antibodies against JEV and these two residues together with the 101 residue were involved in eliciting neutralizing antibodies against JEV and WNV. However, a recent study showed that JEV GIII VLP-expressing plasmids encoding single or double DII FL G106V and L107F mutations performed comparably to the wild-type plasmid in eliciting neutralizing antibodies against JEV ( 39 ). This discrepancy could be due to the use of different amino acids at the DII FL 106 and 107 residues, the method to measure neutralizing antibody titers, or the type of immunogens (VLP vs DNA) used in the study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that JEV GIII VLP-expressing plasmids encoding single or double DII FL G106V and L107F mutations performed comparably to the wild-type plasmid in eliciting neutralizing antibodies against JEV ( 39 ). This discrepancy could be due to the use of different amino acids at the DII FL 106 and 107 residues, the method to measure neutralizing antibody titers, or the type of immunogens (VLP vs DNA) used in the study ( 39 ). By contrast, DENV2 VLP-expressing plasmids encoding DII FL G106R/L107D mutations elicited comparable neutralizing antibodies to the wild-type plasmid by reducing DII FL immunogenicity and manipulating antibody profile ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In WNV serology, a modified FL has been demonstrated to abolish the binding of antibodies induced by heterologous flavivirus infections ( Chabierski et al., 2014 ). In addition, FL-mutated E proteins have been used as parts of virus-like particles (VLPs) in vaccine development against ZIKV, DENV and JEV, resulting in a strong reduction of cross-reactive antibodies ( Crill et al., 2012 ; Richner et al., 2017 ; Kotaki et al., 2022 ). In contrast to these previous vaccine studies, we have used recombinant E ectodomains rather than VLPs, and demonstrate that the WNV E protein with mutated FL significantly reduces the induction of antibodies to heterologous flaviviruses.…”
Section: Discussionmentioning
confidence: 99%